Evolution of the Polyphenolic Content of Moravian White Grape Variety Wines of Different Vintages During Storage - Vašková, R.; Snopek, L.; Mlček, J. (South African Journal of Enology and Viticulture, 2023)
Wine is known as a source of bioactive compounds and is one of the alcoholic beverages with the highest phenolic content. There has been growing interest in the composition of wine due to its beneficial properties for human health. This work focuses on biologically active and sensory attributes of white wine and presents research on wine chemical profiles in relation to their geographical origin, varieties and storage. The aim of this study was to investigate the phenolic compound evolution of 35 selected white wine varieties from the Moravian region in the Czech Republic. To separate and identify individual phenolic compounds in the wines, the high-performance liquid chromatographic method was used. A spectrophotometric method was applied for the determination of total polyphenol and total flavonoid content. This research presents results for the total benzoic and cinnamic acid derivatives, flavonols, flavanols and stilbene content of Moravian white grape varieties. Differences were found in the content of these compounds, and the results show that the phenolic concentrations depend on grape variety and storage time.